2008
DOI: 10.1002/adfm.200800718
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dye Core/Shell Zeolite Nanoparticles: A New Tool for Ratiometric pH Measurements

Abstract: The preparation of core/shell nanoparticles that enable ratiometric pH measurement is described. The core of the nanoparticles consists of a zeolite‐β matrix that exhibits a 3‐hydroxyflavone reference dye within the porous network. Coating an amorphous silica shell containing a fluorosensor around the zeolite through the Stöber process provides pH sensitivity to the nanoparticles. Morphological characterization (dynamic light scattering, transmission electronic microscopy) demonstrates the control of the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 42 publications
0
51
0
2
Order By: Relevance
“…However, most convenient are ion-sensitive fluorophores with ratiometric detection schemes, in which not absolute intensities need to be detected, but the intensities of the emissions at two different wavelengths are compared [56,139]. This can be achieved either by fluorophores with two emission peaks [140] or by combining an ion-sensitive fluorophore which emits at one wavelength with a reference fluorophore which emits at another wavelength [56,141,142]. Thus, in order to determine the ion concentration profile around NPs, ion-sensitive fluorophores (and the reference fluorophores) need to be immobilized at different distances R to the NP surface.…”
Section: Effects Of Ion-induced Nanoenvironments On the Stability Andmentioning
confidence: 99%
“…However, most convenient are ion-sensitive fluorophores with ratiometric detection schemes, in which not absolute intensities need to be detected, but the intensities of the emissions at two different wavelengths are compared [56,139]. This can be achieved either by fluorophores with two emission peaks [140] or by combining an ion-sensitive fluorophore which emits at one wavelength with a reference fluorophore which emits at another wavelength [56,141,142]. Thus, in order to determine the ion concentration profile around NPs, ion-sensitive fluorophores (and the reference fluorophores) need to be immobilized at different distances R to the NP surface.…”
Section: Effects Of Ion-induced Nanoenvironments On the Stability Andmentioning
confidence: 99%
“…[14] There have been some reports on the internalization of ratiometric fluorescence pH nanosensors by cells, [15] with localization of the nanoprobes in the cytoplasm [16] or within acidic organelles. [17] Other studies have reported measurements of a change in intracellular pH values using dual ratiometric fluorescence nanoprobes.…”
mentioning
confidence: 99%
“…Für bioanalytische Nanosensoren wurden KernSchale-Nanopartikel aufgebaut, bei denen im Kern aus Zeolith Beta der Farbstoff Hydroxyflavon und in einer Schale aus SiO 2 -Nanopartikeln der Farbstoff Fluorescein eingelagert sind. Mit diesem System können in lebenden Zellen, Gewebe und Mikroorganismen sehr exakte pHWert-Messungen vorgenommen werden [76]. Weiterhin ist über Veränderungen des Fluoreszenzsignals eines an den Wänden von mesoporösem SiO 2 verankerten und dann in Zellen eingeschleusten Chromophors auch die Detektion von Metallkationen in lebenden Zellen möglich, wie Bhaumik und Mitarbeiter beispielhaft für den Nachweis von Zink-Ionen zeigten [77].…”
Section: +unclassified